PENGEMBANGAN EKONOMI WILAYAH DENGAN PENDEKATAN ANALISIS LOCATION QUETIENS BERDASARKAN KONSEP AGROPOLITAN - Halim, Hasriliandi; Anwar, Desy Rahmawati; Mahmud, Mahmud (Institute of Computer Science (IOCS), 2024)
This research is research on agropolitan-based egional development in improving the community's economy. Agropolitan is one of the theories in regional development. One of the characteristics of regional development using agropolitan theory is that the central place is trade and services, so that the conversion of agricultural land can be more controlled. Basically, it is urban development that is integrated with agricultural development, so that there is an agropolitan area or city in the middle of the garden. The research method used in this research is literature with quantitative analysis by analyzing data taken from the central statistical agency of Soppeng district. The research results show that the development of agropolitan areas in Indonesia, especially in Soppeng Regency, is an important step towards achieving economic development and promoting sustainable development in order to achieve a level of community welfare through the agricultural sector.